Sosialisasi Perhitungan Laporan Keuangan Pada Pelaku UMKM Es Cincau Rohana - Yusuf Yusuf; Budi Ismanto; Asep Suherman (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Community service activities aim to provide socialization of financial statement calculations for Cincau Rohana Ice MSME actors, for business actors and their employees. The methods applied are lecture, practice, and discussion methods. In the lecture method, participants are given material on preparing financial reports in a simple manner. In the practical method, participants are given assistance in accounting process training starting from recording accounting using methods that are easy to remember and understand, up to compiling financial reports and carrying out filing of financial transactions. The discussion method is carried out by asking questions and discussing any problems encountered. The enthusiasm of the participants was quite large as seen from the activeness of the participants in asking questions and the resource persons were quite responsive and communicative in providing solutions